2012
DOI: 10.1509/jm.09.0081
|View full text |Cite
|
Sign up to set email alerts
|

Adding Bricks to Clicks: Predicting the Patterns of Cross-Channel Elasticities over Time

Abstract: The authors propose a conceptual framework to explain whether and when the introduction of a new retail store channel helps or hurts sales in existing direct channels. A conceptual framework separates short-and long-term effects by analyzing the capabilities of a channel that help consumers accomplish their shopping goals. To test the theory, the authors analyze a unique data set from a high-end retailer using matching methods. The authors study the introduction of a retail store and find evidence of cross-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
307
4
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 423 publications
(337 citation statements)
references
References 45 publications
(67 reference statements)
11
307
4
15
Order By: Relevance
“…Inversement, la mobilisation de plusieurs canaux digitalisés altère la valeur perçue de l'offre traditionnelle. Ainsi, à l'instar du rôle de la similarité entre canaux (Dholakia, Zhao et Dholakia, 2005) ou de la congruence entre motivations du consommateur et caractéristiques des canaux (Dorsey, 2006 ;Avery et al, 2012), l'effet des caractéristiques de l'offre et de leur congruence avec les caractéristiques des canaux peut être souligné. Dans un contexte multicanal et multiforme, la valeur perçue de l'offre est fonction du degré de similarité entre canaux mais aussi entre canaux et offres proposées.…”
Section: Iv1 Contributions Théoriques Et Managérialesunclassified
See 2 more Smart Citations
“…Inversement, la mobilisation de plusieurs canaux digitalisés altère la valeur perçue de l'offre traditionnelle. Ainsi, à l'instar du rôle de la similarité entre canaux (Dholakia, Zhao et Dholakia, 2005) ou de la congruence entre motivations du consommateur et caractéristiques des canaux (Dorsey, 2006 ;Avery et al, 2012), l'effet des caractéristiques de l'offre et de leur congruence avec les caractéristiques des canaux peut être souligné. Dans un contexte multicanal et multiforme, la valeur perçue de l'offre est fonction du degré de similarité entre canaux mais aussi entre canaux et offres proposées.…”
Section: Iv1 Contributions Théoriques Et Managérialesunclassified
“…Il est toutefois nécessaire de compléter cette approche utilisateur par une prise en compte des conséquences internes liées au déploiement de ces stratégies multicanal et multiforme, notamment concernant les personnes travaillant à la production de contenu éditorial (par exemple, journalistes et responsables éditoriaux). En effet, la mise en place de telles stratégies peut amener à une segmentation des différents canaux (web, mobile et print) avec des implications fortes sur l'organisation interne du journal et sur la structuration de sa rédaction, comme par exemple l'émergence de différentes communautés de producteurs au sein d'une même entité ou la contrainte de devoir concilier, autour du multimédia, des objectifs et des modes de production parfois complètement opposés (Benghozi et Lyubareva, 2013 ;Utesheva, Simpson et Cecez-Kecmanovic, 2016 Cette recherche invite également les managers à abandonner l'idée d'un déploiement massif, indistinct et non maîtrisé de leur portefeuille de produits et de canaux (Rosenbloom, 2007 ;Avery et al, 2012 (Benghozi et Lyubareva, 2013). (Sundar et al 2014) ou aux affordances (Gibson, 1977 ;Leonardi, 2013) pourrait être utilement mobilisée.…”
Section: Iv1 Contributions Théoriques Et Managérialesunclassified
See 1 more Smart Citation
“…Lee and Gosain (2002) compared these two markets for a homogenous product; music in terms of pricing strategy. Steinfield et al (2002) and Avery et al (2012) underlined the importance of integration and synergy of these two markets. Ward (2001) asked the question 'Will Online Shopping Compete More with Traditional Retailing or Catalog Shopping?'…”
Section: Literature Review and Conceptual Framework Of Researchmentioning
confidence: 99%
“…Barkhi et al (2008) Main assumption of the study is that a person will prefer online shopping or traditional shopping. It is known and suggested that both of these channels are complementary (Farag et al, 2007;Avery et al, 2012). But at data collection phase brick and mortar buyers (who have never used e-shopping) divided precisely from traditional buyers.…”
Section: Literature Review and Conceptual Framework Of Researchmentioning
confidence: 99%